Pengaruh Beban Kerja, Konflik Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. Ara Shoes Indonesia Kabupaten Semarang - Fajar Riyani; Robby Andika Kusumajaya (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
Employee performance is a strategic factor in determining organizational success, particularly in the manufacturing sector, which requires high levels of productivity and work accuracy. This study aims to analyze the effect of workload, work conflict, and work stress on employee performance at PT Ara Shoes Indonesia, Semarang Regency. This research employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to 85 respondents selected using purposive sampling. Data analysis was conducted using SPSS version 25, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that workload, work conflict, and work stress have a significant effect on employee performance, both partially and simultaneously. Workload that exceeds employees’ capacity tends to reduce work effectiveness, while poorly managed work conflict negatively affects the quality of work relationships and productivity. Excessive work stress is also proven to influence employees’ psychological conditions, which in turn leads to a decline in performance. These findings emphasize the importance of comprehensive human resource management through appropriate workload adjustment, constructive conflict management, and effective control of work stress in order to enhance employee performance sustainably.